An Exploratory Study and Impact of Fourth Industrial Revolution (4IR) on SMEs in the Middle East - Alqam, Hanin; Saqib, Mohammed (International Journal of Integrated Engineering, 2020)
The evolution of industrial creation over a period of time can be seen through its first version in 1784 until today 4th Industrial revolution, where cyber-physical system components will communicate with each other using IoT concept. The driving forces of industries are dynamic leadership and emerging technologies. Small and medium enterprises are constantly emerging and facing the challenges of market leaders. Thus there is a need to spot and react immediately seeing the new competitions on the horizon. It is been observed that structure of today will not suit the companies of tomorrow and thus change in the industries and leadership is evolved as 4.0. In this research we have looked at the concept of 4th Industrial Revolution and its impact on SMEs through the leaders of tomorrow. Research also proposed the changes required as robust & strategic planning, acquiring a culture of engaging people, the readiness of SMEs and enhanced communication plans.